Evaluation of Blood Lactate among Different Player Roles: A Pilot Study on Competitive Young Male Soccer Players - Arcone, Rosaria; Montesano, Pietro; Di Silvestro, Maurizio; D'Errico, Antonio; Meccariello, Rosaria; Mazzeo, Filomena (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Soccer match requires anaerobic and aerobic energetic metabolism. The aim of this pilot study was to investigate the changes in blood lactate concentration in young male soccer players in different playing roles at different time points after the soccer match. Methods: Following an initial screening of 134 young soccer athletes, 8 male athletes (average age of 15.5 ± 5 SD) were chosen for their characteristics similar to those of competitive athletes. Players were categorized as goalkeeper, central defender, central midfielder, and forward. Blood lactate concentrations were determined using a portable device at different times (10 min, 5 and 16 h) after the soccer match by a maximum effort test on a treadmill. The data were analyzed by one-way analysis of variance ANOVA, followed by Bonferroni's post-hoc test. Results: The following results (mean ± SD) were obtained: VO2max (%) 60.33 ± 3.10; blood lactate (mM) end match (10 min) 2.17 ± 0.78, post-match-early (after 5 h) 2.2 ± 0.42, postmatch- late (16 h) 3.2 ± 0.84. ANOVA analysis indicated that the blood LA concentrations at end-match (10 min) and post-match-early (5 h) were statistically significative lower than those determined at post-match-late (16 h) (p < 0.05). Conclusion: These results suggest that aerobic mechanisms can also use LA as an energy source, contributing to the reduction of its blood concentration. This effect can be due to reduced maximal work during a soccer match and to the LA removal during exercise at reduced intensity. These data can provide indications for planning suitable training strategies for young male soccer players.
Keywords: energy metabolism